If it ain't broke, don't fix it: When collaborative public management becomes collaborative excess - Elston, T; Bel, G; Wang, H (Wiley, 2023)
Collaboration is a commonly prescribed method of public service improvement. If collaboration fails, blame is typically ascribed to transaction costs, organizational inertia, or premature evaluation. However, drawing on a notable case of collaborative failure in England, we show that misdiagnosing public service problems as being of a type likely to be cured by joint working can also generate poor results, and belongs conceptually prior to many “go-to” explanations of failure. Using stacked difference-in-difference estimators on 11 years of performance data relating to subnational tax administration, we show that inter-municipal cooperation produced no cost or quality improvements in the administration of this public service, contrary to reformer expectations. Supplementary testing attributes this failure less to governance problems, inertia, or precipitate evaluation than to a basic lack of interdependence—the specific “problem” to which collaboration is the “solution”—between partnering councils. Having already exhausted scale economies internally, partners experienced no mutual reliance warranting their attempt to further economize through collaborative tax administration.